2010
DOI: 10.1002/ajmg.b.31065
|View full text |Cite
|
Sign up to set email alerts
|

Sexually dimorphic interaction between the DRD1 and COMT genes in schizophrenia

Abstract: Dopaminergic dysfunction in the prefrontal cortex (PFC) is involved in the pathophysiology of schizophrenia. In the PFC, dopamine signalling largely depends on the D1 receptors, which are coded by the DRD1 gene, and on the regulation of dopamine levels by the enzyme catechol-O-methyltransferase (COMT). Here, we investigate the role of DRD1 and its interaction with the COMT gene in schizophrenic patients. In two gender-limited independent patient and control samples, we genotype five Tag single nucleotide polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Although these data should still be regarded as preliminary, several studies suggest that male patients with high-activity COMT may have greater severity of endophenotypes associated with prefrontal deficits in schizophrenia, such as eye movement disturbances (Rybakowski et al, 2002) prefrontal noise (Winterer et al, 2006) and schizotypal traits (Ma et al, 2007). Similarly, Hoenicka et al (2010) found that the effects of the Val 158 Met polymorphism on schizophrenia vulnerability are more directly related to male patients, possibly through an epistatic interaction with D 1 receptor (Hoenicka et al, 2010) (see below). Other studies indicate that only female carriers of the Val/Met alleles exhibit high propensity to engage in risky behaviors (Amstadter et al, 2012) and alterations in emotional processing (Domschke et al, 2012).…”
Section: The Role Of Daergic Genes In G×s Interactions In Schizophreniamentioning
confidence: 97%
“…Although these data should still be regarded as preliminary, several studies suggest that male patients with high-activity COMT may have greater severity of endophenotypes associated with prefrontal deficits in schizophrenia, such as eye movement disturbances (Rybakowski et al, 2002) prefrontal noise (Winterer et al, 2006) and schizotypal traits (Ma et al, 2007). Similarly, Hoenicka et al (2010) found that the effects of the Val 158 Met polymorphism on schizophrenia vulnerability are more directly related to male patients, possibly through an epistatic interaction with D 1 receptor (Hoenicka et al, 2010) (see below). Other studies indicate that only female carriers of the Val/Met alleles exhibit high propensity to engage in risky behaviors (Amstadter et al, 2012) and alterations in emotional processing (Domschke et al, 2012).…”
Section: The Role Of Daergic Genes In G×s Interactions In Schizophreniamentioning
confidence: 97%
“…Moreover, rs4532 of DRD1 was reported to have an association with performance on tests (e.g., the Wisconsin Card Sorting Test) in patients with schizophrenia (Rybakowski et al, 2005). Very recently, a study using a Spanish population found an association between two individual SNPs (rs11746641 and rs11749676) and haplotypes containing the SNPs in DRD1 and schizophrenia, especially among men (Hoenicka et al, 2010). These findings support the relationship between DRD1 and the pathophysiology of schizophrenia.…”
Section: Discussionmentioning
confidence: 71%
“…Abnormal modulation of dopamine receptor signaling and disorder of dopaminergic nerve function may cause a series of neuropsychiatric defects 36. The DRD1 gene has been considered a potential susceptibility gene for various neuropsychiatric illnesses 9,37,38. Furthermore, several previous studies have reported that the DRD1 gene was associated with alcohol dependence,39 hyperactivity disorders,40 nicotine addiction,41,42 and other behavioral disorders.…”
Section: Discussionmentioning
confidence: 99%
“…First, the sample sizes of several studies included were fairly small and lacked a strong statistical power. Furthermore, the factors of sex38 and age may affect the incidence of the disease. In addition, we didn’t consider the role of different environments, and it is possible that environment may also influence the risk of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%